2023
DOI: 10.1021/acs.est.2c09315
|View full text |Cite
|
Sign up to set email alerts
|

Verification of In Vivo Estrogenic Activity for Four Per- and Polyfluoroalkyl Substances (PFAS) Identified as Estrogen Receptor Agonists via New Approach Methodologies

Abstract: Given concerns about potential toxicological hazards of the thousands of data-poor per-and polyfluorinated alkyl substances (PFAS) currently in commerce and detected in the environment, tiered testing strategies that employ highthroughput in vitro screening as an initial testing tier have been implemented. The present study evaluated the effectiveness of previous in vitro screening for identifying PFAS capable, or incapable, of inducing estrogenic responses in fish exposed in vivo. Fathead minnows (Pimephales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Liu et al found that PFOS could increase mRNA expression of PPARγ, CCAAT/enhancer-binding protein-α (C/EBPα), lipoprotein lipase, and leptin [ 37 ]. Furthermore, animal and in vitro studies have shown that certain PFAS, including PFOA and PFOS, have estrogenic activity and directly interact with estrogen receptors (ERs) [ 38 , 39 , 40 , 41 , 42 , 43 ]. ERs play an important part in energy balance, glucose homeostasis, and lipid metabolism [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that PFOS could increase mRNA expression of PPARγ, CCAAT/enhancer-binding protein-α (C/EBPα), lipoprotein lipase, and leptin [ 37 ]. Furthermore, animal and in vitro studies have shown that certain PFAS, including PFOA and PFOS, have estrogenic activity and directly interact with estrogen receptors (ERs) [ 38 , 39 , 40 , 41 , 42 , 43 ]. ERs play an important part in energy balance, glucose homeostasis, and lipid metabolism [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Per- and polyfluoroalkyl substances (PFAS) are a large class of fluorinated organic chemicals that are ubiquitous and persistent in humans and the environment and are thus of interest to regulatory agencies and the general public. Multiple PFAS have been identified as potential endocrine-disrupting chemicals [ 1 ] due to estrogen receptor activation [ 2 , 3 , 4 ], impacts on puberty timing [ 5 , 6 , 7 , 8 ]. In this study, the uterotrophic assay was used to address the impact of PFAS as a mammalian endocrine disruptor.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in other labs identified PFAS with estrogenic activation in fish or estrogen receptor activation with in vitro screens. Villeneuve et al [ 7 ] used tiered testing, starting with in vitro estrogen receptor screening and further testing in fish for the estrogen sensitive endpoint of vitellogenin activation. Of the five PFAS (perfluorooctanoic acid [PFOA]; 1H,1H,8H,8H-perfluorooctane-1,8-diol [FC8-diol]; 1H,1H,10H,10H-perfluorodecane-1,10-diol [FC10-diol]; 1H,1H,8H,8H-perfluoro-3,6-dioxaoctane-1,8-diol [FC8-DOD]; and perfluoro-2-methyl-3-oxahexanoic acid [HFPO-DA]) that were positive estrogen receptor activators in vitro, only three induced vitellogenin activation (FC8-diol, FC10-diol, and FC8-DOD) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations